Harvest timing and cultivar effects on phenolics and volatiles in bergamot juice and essential oil - ANTONIO GATTUSO; ROCCO MAFRICA; DAVIDE MAFRICA; ALESSANDRA DE BRUNO; MARCO POIANA (Smujo International, 2025)
Abstract. Gattuso A, Mafrica R, Mafrica D, De Bruno A, Poiana M. 2025. Harvest timing and cultivar effects on phenolics and volatiles in bergamot juice and essential oil. Asian J Agric 9: 889-897. Bergamot (Citrus bergamia) is traditionally cultivated for essential oil production, but increasing interest in its health-promoting properties has enhanced the relevance of juice and derived products. However, the combined influence of harvest time and cultivar on the seasonal evolution of phenolic compounds in juice and volatile constituents in essential oil remains insufficiently defined. This study investigated these changes in the two main Protected Designation of Origin (PDO) cultivars, ‘Fantastico’ and ‘Femminello’. Fruits were collected monthly from November to June, and phenolic compounds in juice and volatile constituents of essential oil were analyzed in parallel using UHPLC-DAD and GC-FID, respectively. Significant differences were observed both between cultivars and across ripening stages. Phenolic compounds in bergamot juice increased progressively during the harvest season, with higher late-season accumulation in ‘Femminello,’ reflecting both enhanced biosynthesis and dilution-concentration effects associated with fruit growth. In essential oil, ripening was characterized by a marked decrease in monoterpene alcohols and a concomitant increase in acetate esters, indicating a seasonal shift that strongly influences aromatic quality. Early harvests yielded oils richer in linalool and fresher aromatic notes, whereas mid- to late-season harvests were associated with higher ester content and smoother, more persistent fragrance profiles. These findings provide the first integrated, month-by-month characterization of phenolic and volatile dynamics in the two main bergamot cultivars. By linking biochemical evolution to harvest timing, the results offer practical guidance for defining cultivar-specific harvest windows aimed at maximizing functional phytochemicals in juice and tailoring the aromatic profile of essential oil, thereby supporting improved decision-making in bergamot production and processing.